Definition of ‘close contacts’ in leprosy studies: protocol for a scoping review [version 1; peer review: 2 approved, 1 approved with reservations] - Koen Peeters Grietens; Kristien Verdonck; Claudia Nieto-Sanchez; Sien De Coninck; Maya Ronse (F1000Research, 2022)
Despite difficulties to document transmission pathways (assumed to be airborne), increased risk of leprosy infection has been shown for individuals living in close contact with patients. However, variations in the concept of ‘close contacts’ are used in different settings and studies. We conduct this review to identify criteria of space (location, geographical variables, distance, indoor vs outdoor), time (including frequency and duration), physical exposure (skin to skin, sexual), and relationship (familial, occupational, social) involved in the definition of ‘close contacts’ in leprosy studies. We expect this review to provide an overview of the (lack of) conceptualization of this term and its variations across settings. Primary studies and reviews are eligible for inclusion in this review. The main source of records will be the PubMed interface. Secondary searches will be conducted in Google Scholar, as well as through the reference lists of selected publications. The search strategy is based on the combination of the condition of interest (leprosy) and the concept under study (‘contact’). The findings of this review will be presented using thematic narrative synthesis, tables, and figures. The protocol is written in line with the Prisma Extension for Scoping reviews (PRISMA-ScR).